The diagnosis, prevalence and prognosis of delirium in an older hospital population - Whittamore, Katherine H. (2012)
Delirium is a syndrome which is characterised by a change in cognition, attentional difficulties and alterations to the sleep-wake cycle. In most cases it is caused by the onset of a physical illness. Delirium is more commonly found in older people aged 65 years or older, with prevalence in hospital being as high as 42%. Delirium is associated with negative outcomes such as increased length of hospital admissions, institutionalisation and mortality.